1994
DOI: 10.1007/bf00871642
|View full text |Cite
|
Sign up to set email alerts
|

Reductive dehalogenation as a respiratory process

Abstract: Anaerobic bacteria can reductively dehalogenate aliphatic and aromatic halogenated compounds in a respiratory process. Only a few of these bacteria have been isolated in pure cultures. However, long acclimation periods, substrate specificity, high dehalogenation rates, and the possibility to enrich for the dehalogenation activity by subcultivation in media containing an electron donor indicate that many of the reductive dehalogenations in the environment are catalyzed by specific bacteria. Molecular hydrogen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
94
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 49 publications
1
94
0
1
Order By: Relevance
“…''Dehalobacter restrictus'' was isolated from a fixed-bed column fed with lactate and PCE (10) and exclusively utilizes H 2 as an electron donor and PCE and TCE as electron acceptors (11). The reducing equivalents derived from oxidation of H 2 have been shown to be quantitatively recovered in dechlorination products and biomass (10).…”
Section: Cis-dcementioning
confidence: 99%
See 2 more Smart Citations
“…''Dehalobacter restrictus'' was isolated from a fixed-bed column fed with lactate and PCE (10) and exclusively utilizes H 2 as an electron donor and PCE and TCE as electron acceptors (11). The reducing equivalents derived from oxidation of H 2 have been shown to be quantitatively recovered in dechlorination products and biomass (10).…”
Section: Cis-dcementioning
confidence: 99%
“…Preliminary experiments suggested that the two enzymes in ''D. restrictus'' are arranged in the third way (11). The formation of two protons at the outside of the cell upon H 2 oxidation by a periplasmically oriented hydrogenase and the concomitant transmembrane transport of two electrons to a cytoplasmically oriented PCE reductase were suggested as the mechanism to generate a proton electrochemical potential (11).…”
Section: Cis-dcementioning
confidence: 99%
See 1 more Smart Citation
“…strain PCEl (Gerritse et al, 1996), Desulfitobacterium sp. strain PCE-S (Miller et al, 1997;Miller et al, 1998), Desulfomonile tiedjei (Fathepure et al, 1987;DeWeerd et al, 1990), Dehalobacter restrictus (HoUiger and Schumacher, 1994;Holliger et al, 1998), strain TT4B (Krumholz et al, 1996), and the facultative organism strain MS-1 (Sharma and McCarty, 1996). With the exception oiDehalococcoides ethenogenes which dechlorinates PCE to ethene, and Desulfitobacterium sp.…”
Section: >9=mentioning
confidence: 99%
“…Both laboratory studies and field observations suggest that the addition of electron donors for the enhancement of dechlorination can induce complex scenarios that are a function of the subsurface conditions (Carr and Hughes, 1998;Fennell and Gossett, 1997) and the indigenous microbial population (Gibson and Sewell, 1992). Although it is known that hydrogen serves as the specific electron donor for reductive dechlorination (HoUiger et al, 1993;HoUiger and Schumacher, 1994;Maymo-Gatell et al, 1995), different concentrations of hydrogen stimulate different groups of anaerobic microbial populations which may or may not be responsible for dechlorination, and may out compete the halorespirers, making the direct addition of hydrogen problematic. In fact, recent research has indicated that dechlorinating bacteria possess lower half-velocity coefficients for Ha utilization than methanogens, suggesting that dechlorinating bacteria should out compete methanogens at low Ha concentrations (Ballapragadaetal., 1997;SmatlaketaL, 1996).…”
Section: >9=mentioning
confidence: 99%